Water Management, Communities, and Environment. The Low Countries in Comparative Perspective, c. 1000 - c. 1800 - Greefs, Hilde; 't Hart, Marjolein (Gent: Academia Press; Hilversum: Verloren, 2006)
"Themaredactie Hilde Greefs en Marjolein 't Hart"